2017
DOI: 10.1159/000485291
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of CAVEOLIN-1 Sensitizes Human Basal-Like Triple-Negative Breast Cancer Cells to Radiation

Abstract: Background/Aims: Triple-negative breast cancer (TNBC) is a high-risk breast cancer phenotype without specific targeted therapy options and is significantly associated with increased local recurrence in patients treated with radiotherapy. CAVEOLIN-1 (CAV-1)-mediated epidermal growth factor receptor (EGFR) nuclear translocation following irradiation promotes DNA repair and thus induces radiation resistance. In this study, we aimed to determine whether knockdown of CAV-1 enhances the radiosensitivity of basal-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 50 publications
6
19
0
Order By: Relevance
“…86 Herein, CAV1 was found to be overexpressed in TNBC cell lines and CAV1 expression levels correlated with the sensitivity to IR. 86 The more radiosensitive low CAV1-expressing or CAV1-negative cells were characterized by an impaired RTinduced nuclear EGFR translocation, pronounced DNA damage and apoptosis. CAV1 silencing limited the radiationinduced elevation of DNA repair proteins, subsequently leading to sustained DNA damage and finally resulting in increased apoptosis.…”
Section: -Stromal Bone Marrow Cells Induce Cav1 Expression In Cll Celmentioning
confidence: 82%
“…86 Herein, CAV1 was found to be overexpressed in TNBC cell lines and CAV1 expression levels correlated with the sensitivity to IR. 86 The more radiosensitive low CAV1-expressing or CAV1-negative cells were characterized by an impaired RTinduced nuclear EGFR translocation, pronounced DNA damage and apoptosis. CAV1 silencing limited the radiationinduced elevation of DNA repair proteins, subsequently leading to sustained DNA damage and finally resulting in increased apoptosis.…”
Section: -Stromal Bone Marrow Cells Induce Cav1 Expression In Cll Celmentioning
confidence: 82%
“…Breast cancer remains a leading cause of cancer-related death in women [1][2][3]. Despite increased screening and improved diagnosis and treatment of breast cancer, prognosis remains poor [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In phase 3 clinical trials, radiation in combination with the molecular-targeted epidermal growth factor receptor (EGFR) inhibitor cetuximab led to a survival benefit of 10% in patients with HNSCC [3]. Delayed EGFR nuclear accumulation by downregulation of caveolin-1 increased radiosensitivity in breast cancer [86]. In preclinical models, PI3K/mTOR inhibitor enhances HNSCC radiosensitivity [87].…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that Wnt1 signaling inhibits cancer therapy-induced apoptosis by inhibiting cytochrome c release and activation of caspase-9 [84]. In addition, inhibition of β-catenin in head and neck squamous cell carcinoma (HNSCC) induced the activation of caspase-3, increased p53 and the proapoptotic protein Bax, and reduced the anti-apoptotic protein Bcl-2 [86]. Wnt-1-induced secreted protein, as an important downstream target gene of Wnt1/β-catenin signaling, prevents p53-mediated apoptosis, inhibits the mitochondrial release of cytochrome c, and elevates the expression of anti-apoptotic protein Bcl-X L in cancer [52].…”
Section: Apoptosismentioning
confidence: 99%